Starch utilization routes in lactic acid bacteria: New insight by gene expression assay. (6th May 2016) - Velikova, Petya; Stoyanov, Anton; Blagoeva, Galya; Popova, Luiza; Petrov, Kaloyan; Gotcheva, Velitchka; Angelov, Angel; Petrova, Penka
Abstract : The annotation of full genomes of amylolytic lactic acid bacteria (ALAB) leads to conviction that many of them contain a basic pool of chromosomal genes, responsible for starch hydrolysis. However, only the strains that are forced to survive in starchy environment are able to display these genetically determined properties. The aim of the present work is to investigate the genes actually engaged in starch utilization by ALAB using gene transcription assay. Twenty five new ALAB strains, belonging to 11 distinct species of four genera were isolated and analyzed. Among them, the first amylolytic Lactobacillus sakei, Enterococcus faecium, and E. durans were reported. The presence and expression of the genes amy1, glgP, glgB, agl, malL, treC, and dexC were examined. Although all strains possessed extracellular and cell‐bound amylase activity and produced lactic acid from starch, high genus and species specificity in the gene expression was observed. ALAB strains of genus Lactobacillus (except L. sakei ) and P. acidilactici own and express all the tested genes, while E. faecium and E. durans strains expressed predominantly the gene, encoding amylase. The co‐transcription of glgP and glgB genes indicates that glycogen synthesis and starch degradation occur in parallel, which is another example for dual metabolic role of biochemical paths.